The Influence of Work Motivation, Compensation, and Work Engagement on Performance with Job Satisfaction as an Intervening Variable at the Central Statistics Agency of Central Kalimantan Province - Waluyo Wicaksono; Ida Ariyani; Ami Pujiwati (Journal Research of Social Science, Economics, and Management, 2025)
This study examines the influence of Work Motivation, Compensation, and Work Involvement on Performance, mediated by Job Satisfaction, among employees of the Central Statistics Agency of Central Kalimantan Province. Employing a quantitative, correlational approach, the research involved 380 employees, with 170 respondents selected using a saturated sampling technique. Data were gathered through questionnaires and analyzed using Structural Equation Modeling (SEM) via AMOS, supported by descriptive analysis with Microsoft Excel and SPSS. Descriptive results indicate that the average responses for Performance, Job Satisfaction, Work Motivation, and Compensation were categorized as “agree,” while Work Involvement was rated “strongly agree.” The modified AMOS model produced the following structural equations: Job Satisfaction (KEP) = -0.002?Work Motivation (MK) - 0.025?Compensation (KOM) + 0.918?Work Involvement (KK), R²?=?0.802; Performance (KIN) = 0.776?Job Satisfaction (KEP) + 0.095?Work Motivation (MK) + 0.180?Compensation (KOM) - 0.017?Work Involvement (KK), R²?=?0.901. The findings reveal that Work Motivation does not significantly influence Job Satisfaction and does not directly affect Performance, though it has an indirect impact through Job Satisfaction. Job Satisfaction significantly affects Performance, while Compensation shows no significant relationship with either variable. Work Engagement strongly affects Job Satisfaction but not Performance. Collectively, Work Motivation, Compensation, and Work Involvement explain 80.2% of Job Satisfaction variance and 90.1% of Performance variance.